(untitled) (Indonesian Tourism Justice Review, 2025)
The tourism industry in Indonesia, particularly in tourist-heavy regions like Bali and Yogyakarta, has become a focal point for gender-based exploitation, with women often facing multiple layers of discrimination and unequal labor conditions. This paper explores the intersection of gender and tourism, examining how gendered expectations within the hospitality sector contribute to the marginalization and exploitation of women. The study focuses on sex tourism, gender-based labor exploitation, and the societal pressures placed on women to conform to traditional roles within the tourism industry. Using qualitative interviews with women working in various sectors of tourism—including hotels, bars, and tour agencies—the paper explores the challenges women face in achieving economic justice. It also highlights the role of local and national policies in either perpetuating or mitigating these gender disparities. The paper concludes with recommendations for tourism stakeholders to implement gender-sensitive policies that promote fair wages, career opportunities, and greater protection against exploitation.